OPTIMALISASI HILIRISASI, KETAHANAN PANGAN, DAN REFORMASI FISKAL SEBAGAI PILAR TRANSFORMASI EKONOMI MENUJU INDONESIA EMAS 2045 - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2025)
This study examines the optimal role of downstreaming, food security, and fiscal reform as key pillars in Indonesia's economic transformation towards the Indonesia Emas 2045 vision. Downstreaming is identified as an important strategy to increase the added value of domestic products and promote sustainable industrialisation. Food security is the foundation of national social and economic stability through the provision of sufficient, high-quality, and sustainable food. Meanwhile, fiscal reform ensures the availability of effective policies and financing capacity to support the two pillars through a more efficient and fair taxation system and budget management. This literature review examines various related literature to describe the current conditions, challenges, and opportunities for implementing the three pillars in the context of national economic development. The results of the study emphasise the need for synergy and an integrative approach to the three pillars so that Indonesia can achieve a self-reliant, inclusive, and globally competitive economic transformation by 2045.